Enhancing 3D Printing Agriculture Drone Design Through Structural Optimisation - Mohd Zaki, Ahmad Syahir; Omar Mohd Faizan Marwah, (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This research investigates a comprehensive analysis and optimization of drone design, focusing on structural integrity and aerodynamic performance. The study employs advanced materials like carbon fiber and Nylon 6/10, integrating additive manufacturing techniques to enhance the durability, efficiency, and overall performance of drones. Through structural and aerodynamic analysis, the research identifies critical factors influencing drone stability and control, such as material properties, design configurations, and environmental conditions. The results demonstrate significant improvements in flight performance and energy efficiency, highlighting the potential of optimized drone designs for various applications, including commercial, industrial, and agricultural uses. The findings underscore the importance of a holistic approach to drone design, combining structural integrity with aerodynamic efficiency to achieve superior performance and reliability.